Chemically modified mRNA beyond COVID-19: Potential preventive and therapeutic applications for targeting chronic diseases - Dana Elkhalifa (Elsevier, 2022)
Chemically modified mRNA represents a unique, efficient, and straightforward approach to produce a class of biopharmaceutical agents. It has been already approved as a vaccination-based method for targeting SARS-CoV-2 virus. The COVID-19 pandemic has highlighted the prospect of synthetic modified mRNA to efficiently and safely combat various diseases. Recently, various optimization advances have been adopted to overcome the limitations associated with conventional gene therapeutics leading to wide-ranging applications in different disease conditions. This review sheds light on emerging directions of chemically modified mRNAs to prevent and treat widespread chronic diseases, including metabolic disorders, cancer vaccination and immunotherapy, musculoskeletal disorders, respiratory conditions, cardiovascular diseases, and liver diseases.